EXPLORING THE NEXUS OF ALLIANCE ORIENTATION, TA’AWUN, AND INNOVATION PERFORMANCE: A CONCEPTUAL ANALYSIS FOR MANUFACTURING SMES - Noor Hasvenda Abd Rahim; Hasliza Abdul Halim (International Journal of Accounting, Finance and Business, 2023)
Small and medium-sized enterprises (SMEs) in the manufacturing sector face significant challenges in maintaining innovation performance in the dynamic business environment. Engaging with external partners by maintaining a diverse portfolio of alliances can be a promising strategy to enhance innovation performance. Innovation drives growth by introducing new ideas, technologies, and processes to organisations. However, interorganisational relationships have drawbacks, such as failure traps, trust-based issues, and shorter alliance life cycles. To address these challenges, the concept of ta'awun promotes mutual collaboration and support, grounded in Islamic teachings and values. It bridges the gap in complex business relationships. Ta'awun embodies diversity in business partnership, functionality and governance while preventing illegal and harmful activities, in accordance with Shariah perspectives. This study proposes perspectives on ta’awun portfolio diversity through the lens of relational view theory. It aims to propose a conceptual model that explores the role of ta'awun as a mediator between alliance orientation and innovation performance for SMEs. Additionally, it contributes to literature by providing insights into the importance of ta'awun as an additional factor in addition to contemporary interorganisational relationship studies. This effort can potentially pave the way to enhance resources and capabilities by incorporating a stronger spiritual Islamic stance into business practices, ultimately improving innovation performance.